Photocatalytic oxidation of volatile organic compounds (VOCS) in air using based materials - Othman, Mohd. Yusuf (Universiti Teknologi Malaysia, 2003)
Heterogeneous photocatalytic oxidation is a promising technique for the removal of volatile organic pollutants (VOCs). It allows the oxidation of gaseous VOCs into carbon dioxide and water in the presence of semiconductor catalyt and UV light. Titanium dioxide (TiO2) represents one of the most efficient photocatalyst. It is chemically stable, non-toxide and low cost. However, the photoexcitation processes of pure TiO2 is only active in the ultra violet fraction of the solar irradiation and although, TiO2 can treate a wide range of VOCs, the effectiveness of the process for the population abatement is still low. Doping TiO2 with metal ions was considered as an alternative method to improve TiO2 photocatalytic properties. In this study, transparent TiO2 thin films were also prepared using the sol-gel and dip-coating method. Various ratios of doped TiO2 thin films were prepared using Cr3+